2019
DOI: 10.1016/j.wear.2018.12.035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frequency on both the debris and the development of the tribologically transformed structure during fretting wear of a high strength steel

Abstract: Confirmation of AuthorshipPlease save a copy of this MS Word file, complete and upload as the "Confirmation of Authorship" file.As corresponding author, I Adam Kirk, hereby confirm on behalf of all authors that:1) The authors have obtained the necessary authority for publication.2) The paper has not been published previously, that it is not under consideration for publication elsewhere, and that if accepted it will not be published elsewhere in the same form, in English or in any other language, without the wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…This very nice correlation involving a wide range of experiments confirms the stability of the model and comes in agreement with the contact oxygenation concept (COC) which suggests that the higher the Archard power density dissipated in the contact, the faster the consumption of di-oxygen molecules and consequently the smaller the oxygen distance. Similar tendency was observed in previous studies on titanium [9,10] and steel alloys [58]. The given results are established for the studied steel interface.…”
Section: Variable Contact Pressure (P)supporting
confidence: 91%
“…This very nice correlation involving a wide range of experiments confirms the stability of the model and comes in agreement with the contact oxygenation concept (COC) which suggests that the higher the Archard power density dissipated in the contact, the faster the consumption of di-oxygen molecules and consequently the smaller the oxygen distance. Similar tendency was observed in previous studies on titanium [9,10] and steel alloys [58]. The given results are established for the studied steel interface.…”
Section: Variable Contact Pressure (P)supporting
confidence: 91%
“…Fretting is defined as small amplitude relative oscillatory motion between two contacting bodies that gives rise to both wear and fatigue in a wide range of industrial contexts, the understanding and mitigation of which have been the subject of extensive study. It is well known that fretting conditions can result in substantial subsurface damage [1,2], and in contrast to sliding wear, the small relative displacements that characterise fretting have a significant impact on the development of wear through the behaviour of wear debris in the contact itself; specifically, a proportion of wear debris is entrapped in the contact and thus modifies the nature of the contact, whilst the remaining debris is ejected from the contact and thus ceases to play a direct role in the subsequent wear process [3].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that seems to have a great influence in fretting wear mechanisms is the frequency. Kirk et al [29] conducted fretting wear experiments using high strength steels in the cylinder-on-flat configuration across a range of frequencies. They observed that, for higher frequencies, the wear damage was lower than for lower ones.…”
Section: Motivation and The State Of The Artmentioning
confidence: 99%